Diffusion MR Imaging of Hypoglycemic Encephalopathy - Kang, E.G.; Jeon, S.J.; Choi, S.S.; Song, C.J.; Yu, I.K. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: MR imaging features of HE have not been fully established. The purpose of this study was to determine the topographic distribution and DWI findings of HE. MATERIALS AND METHODS: We retrospectively evaluated HE MR imaging (n = 11). The topographic distribution of the lesions was evaluated on routine MR imaging, and DWI SI and ADC values were assessed. The ADC value of involved lesions was compared with the noninvolved subcortical WM area by use of the paired t test. RESULTS: MR images demonstrated bilateral diffusion-restrictive lesions in the posterior limb of the IC (n = 6), cerebral cortex (n = 8), CR (n = 7), CS (n = 9), hippocampus (n = 4), and BG (n = 1). The mean ADC value of lesions was 448.82 ± 92.34 × 10−6 mm2/s compared with the mean ADC value of noninvolved lesions (837.72 ± 62.14 × 10−6 mm2/s); this difference was statistically significant (P < .000). The lesions showed complete resolution on follow-up DWI for 6 patients. Three patients with cortical involvement of ≥2 lobes showed partial recovery or death, but most of the other patients with WM involvement or cortical involvement in only 1 lobe experienced complete recovery. CONCLUSIONS: The topographic localization of the lesions was the posterior limb of the IC, cerebral cortex, CR, CS, hippocampus, and BG. Most HE lesions probably correspond to areas of reversible cytotoxic edema as seen on DWI, which can predict the prognosis of HE according to the degree of lesion extent. ADCapparent diffusion coefficientAPNacute pyelonephritisBGbasal gangliaBSTblood sugar testCCcorpus callosumCRcorona radiataCScentrum semiovaleDMdiabetes mellitusDWIdiffusion-weighted imageFLAIRfluid-attenuated inversion recoveryFLfrontal lobeHEhypoglycemic encephalopathyICinternal capsuleINinsular lobeMCAmiddle cerebral arteryMRIMR imagingNSAnumber of signals averagedOCoccipital lobePAparietal lobeSIsignal intensityTLtemporal lobeWMwhite matter